Patterns of Post-endoscopic Retrograde Cholangiopancreatography (ERCP) Complications - Habib, Md Rehan; Ahmed, Farid; Gain, Gobinda; Hasan, Rashedul; Ishaque, SM; Ahmed, Dewan Saifuddin (Bangladesh Medical Journal, 2022)
In the treatment of common bile duct stones and palliative decompression of malignant strictures, endoscopic retrograde cholangiopancreatography (ERCP) is the gold standard. However, there are still concerns about procedure-related complications and patient discomfort. The aim of the study is to evaluate the pattern of post ERCP complications. This prospective observational study was conducted at the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from February to October 2017. A total of one hundred patients who were eligible for ERCP were included in this study but five patients were excluded due to cannulation failure. Clinical examination , biochemical, and radiological investigation were performed before and after ERCP to assess the complication that occurred. The majority of patients in this study were at and below the age of 50 years, with a mean age of 49.74 ± 14.07 years and the age range was between 18 to 80 years. Majority of the subjects were male (54.7%), and male to female ratio was 1.21:1. The highest number of patients were diagnosed as choledocholithiasis (58.9%) followed by proximal cholangiocarcinoma (13.7%), Ca-gallbladder with biliary infiltration (8.4%), Distal cholangiocarcinoma (6.3%), Chronic calcific pancreatitis and Periampullary carcinoma each (3.2%), Suspected SOD & Chronic pancreatitis each (2.1%) and Worm in CBD and benign biliary stricture each (1.1%). In this study, the overall post-ERCP complication was 12.6%, with pancreatitis accounting for 9.4%, bleeding accounting for 2.1%, and cholangitis accounting for 2.1%. From the study, it can be concluded that pancreatitis is the most frequent Post-ERCP complication. Bangladesh Med J. 2021 May; 50(2) : 35-39